Export Diversification and Competitiveness: Nepal’s Experiences - Pant, Bhubanesh; Panta, Rajan Krishna (NRB Economic Review, 2009)
Nepal’s policy regime has not been very instrumental in improving trade competitiveness. Although policy measures have been announced from time to time to identify new exportable products and encourage diversification of export markets, these have hardly been executed. The challenge for Nepal is complicated by the legacy of the past. Against this perspective, this paper a) examines the export scenario of Nepal and reviews the past studies on the country's export potential; b) illustrates Nepal's competitiveness of the export sector; and c) suggests measures for promoting export diversification and competitiveness. Based on the estimation of the real effective exchange rate (REER), this paper shows that the country is gradually losing its competitiveness. Although various studies have demonstrated that Nepal possesses competitive advantage in herbal products, woollen carpets, tea, garments and pashmina, among others, a comprehensive case-by-case analysis of home and host countries trading environment, supply and demand conditions, cost of production, capacity to innovate, as well as its forward and backward linkages should be conducted to translate the export potential to the actual trading opportunities.